Combating Unrecorded Alcohol Through Law Enforcement: A Case Study in Greater Bandung - Mercyta Jorsvinna Glorya; Kidung Asmara Sigit (Center for Indonesian Policy Studies (CIPS), 2019)
CIPS has published Combating Unrecorded Alcohol Through Law Enforcement: A Case Study in Greater Bandung. In our latest paper, we outline policy reforms needed to address the high number of fatalities from illegal alcohol consumption that have affected Bandung in recent years. The paper argues to reduce restrictions on safe and legal alcohol to divert consumers from seeking alcohol in black markets, and improved education and law enforcement efforts on responsible legal alcohol consumption in the interest of public health and safety.
Keywords: 330